Factores que influencian la adopción de criptomonedas en los mercados financieros como forma de pago digital o inversión - Ortiz Segura, William Carlos (2025)
The purpose of this study is to conduct a systematic review of the available literature to identify, analyze, and synthesize the most relevant factors that could influence the adoption of cryptocurrencies in financial markets as a form of digital payment or investment. To this end, a search was conducted in databases such as Scopus, Web of Science, Redalyc, SciELO, Alicia Concytec, and Google Scholar. Twenty-nine open-access empirical papers were selected using the PRISMA methodology, with a predominance of international studies. The results show that the adoption of cryptocurrencies is a multidimensional phenomenon influenced by technological, economic, social, demographic, regulatory, and psychological-behavioral factors. The most recurrent variables include security, traceability, transaction processing, perceived value, price value, financial literacy, perceived risk, subjective norms, herd behavior, government policies, perceived ease of use, perceived usefulness, awareness, trust, and attitude. This study provides a conceptual basis for understanding cryptocurrency adoption as an emerging phenomenon within financial markets and highlights the need for applied research in the Peruvian context, where cryptocurrency use is still emerging and where there is little scientific evidence revealing adoption patterns.